Proceedings of the International Conference on Information Technology & Systems (ICITS 2018) - Rocha, Álvaro; Guarda, Teresa; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book includes a selection of articles from the 2018 International Conference on Information Technology & Systems (ICITS 18), held on January 10 - 12, 2018, at the Universidad Estatal Península de Santa Elena, Libertad City, Ecuador.   ICIST is a global forum for researchers and practitioners to present and discuss recent findings and innovations, current trends, lessons learned and the challenges of modern information technology and systems research, together with their technological development and applications.   The main topics covered include information and knowledge management; organizational models and information systems; software and systems modeling; software systems, architectures, applications and tools; multimedia systems and applications; computer networks, mobility and pervasive systems; intelligent and decision support systems; big data analytics and applications; human-computer interaction; ethics, computers & security; health informatics; and information technologies in education.
Part I: Organizational Models and Information Systems -- Rationalization of Organizational Processes: The case of the Institute of Applied Social Sciences of Rio de Janeiro Federal Rural University -- Benefits of Process Simulation Software - The case of a Brazilian mixed public-private company -- IT Service Management using COBIT enablers: The Case of Brazilian National Institute of Cancer -- Towards a Forensic Analysis of Mobile Devices using Android -- Process-Based Project Management for Implementation of an ERP System at a Brazilian Teaching Institution -- A conceptual framework for the implantation of Enterprise Applications in Small and Medium Enterprises (SMEs) -- Model for Selecting Software Development Methodology -- Part II: Information and Knowledge Management -- Smart Cities Semantics and Data Models -- The information technologies in the competitiveness of the Tourism sector.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence